2012
DOI: 10.1002/hep.24738
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus (HEV)-specific T-cell responses are associated with control of HEV infection

Abstract: Hepatitis E virus (HEV) infection is usually self-limited but may lead to acute hepatitis and rarely to fulminant hepatic failure. Persistent HEV infections have recently been described in organ transplant recipients receiving immunosuppressive medications, suggesting that HEV is controlled by adaptive immune responses. However, only few studies have investigated HEV-specific T-cell responses and immune correlates for the failure to clear HEV infection have not been established so far. We investigated T-cell r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
168
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(185 citation statements)
references
References 48 publications
(70 reference statements)
13
168
1
3
Order By: Relevance
“…The M domain contains T cell epitopes (1). Thus, the immune pressure mediated by T cells could explain the difference in selection, since the T cell response determines HEV eradication (33). An effective immune response should lead to less conservation of amino acid sequences, which is in line with our observations.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The M domain contains T cell epitopes (1). Thus, the immune pressure mediated by T cells could explain the difference in selection, since the T cell response determines HEV eradication (33). An effective immune response should lead to less conservation of amino acid sequences, which is in line with our observations.…”
Section: Discussionsupporting
confidence: 88%
“…Since the virus is not cytolytic, the elimination of infected hepatocytes may depend on the degree of T cell activation. Patients who cleared their HEV infection after transplantation have been found to have a strong, HEV-specific T cell response (33). We found that the serum concentrations of five chemokines were higher in those patients whose HEV infection became chronic.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…10 It is known to be non-enveloped in bile and faeces, and is present in blood, coated in a lipid membrane. HEV consists of a 5' short noncoding region (NCR), ORF1 (which encodes the nonstructural proteins), ORF3 (which encodes a small multifunctional protein), ORF2…”
Section: The Molecular Biology Of Hepatitis E Virusmentioning
confidence: 99%
“…The development of a chronic HEV infection also seems to be associated with a weak inflammatory response, poor Tcell activation, and high serum concentrations of the chemokines involved in leukocyte recruitment to the liver (7). Another study reported that the evolution to chronic infection is associated with an impaired specific T-cell response (9).…”
mentioning
confidence: 99%